Education of information professionals - Croatian perspective - Tkalac, Slavko; Lasić-Lazić, Jadranka; Slavić, Aida Lazić, Nikolaj; Vučković, Kristina (1999)
The paper will examine a conception of LIS education in the curricula of Department of Information Science at the University of Zagreb. The curricula of this department is specific in a way it views the field of information science and embraces four different profiles of information professionals within one undergraduate programme. It will be explained how different profiles see their role and realise their mission within the department curricula. The conception of information science school which provides good foundation of the study of information society and satisfies a complex role of the future professionals in the libraries, archives, museums and schools.
Projekt MZOS
ENG